(untitled) (Web of Teachers: Inderscience Research, 2026)
This article reflects the social processes related to the role of the idea of democracy in the social factors of democratization and sustainable development of society, the protection of national interests in international socio-political relations, the fact that this responsibility is assigned to the main political institution of society - the state - and is enshrined in its Constitution, the process of satisfying the needs of states within the system of international relations, and the basis for implementing the strategic goals of protecting national interests.